A lifetime of learning: Dorothy Helema’s journey with Conservation Agriculture in Malawi - Kudzanai Chimhanda (CIMMYT, 2025)
Dorothy Helema is turning personal loss into lasting legacy, transforming Conservation Agriculture from a research concept into a thriving community movement—one trial plot at a time.